Investigating the Antibacterial Effect of Passive Ultrasonic Irrigation, Photodynamic Therapy and Their Combination on Root Canal Disinfection: PUI, PDT and PUI/PDT Effect on Root Canal Disinfection - Ahangari, Zohreh; Asnaashari, Mohammad; Akbarian Rad, Nazila; Shokri, Mehdi; Azari-Marhabi, Saranaz; Asnaashari, Negin (Journal of Lasers in Medical Sciences, 2021)
Introduction: Enterococcus faecalis is a gram-positive, facultative anaerobic bacterium associated with persistent endodontic infections. Conventional disinfection methods may not completely eradicate the bacteria within the root canal system. Therefore, novel modalities have been suggested to optimize root canal disinfection. The aim of this study was to evaluate and compare the antibacterial effect of photodynamic therapy (PDT), passive ultrasonic irrigation (PUI) and their combination in addition to conventional endodontic irrigation against E. faecalis biofilms in root canals. Methods: Root canals of 50 single-rooted extracted human teeth were prepared and incubated with E. faecalis for 21 days. They were then divided into 4 treatment groups and a control group as follows: (1) NaOCl—Syringe irrigation with 2.5% NaOCl, (2) PUI—Passive ultrasonic irrigation with NaOCl, (3) NaOCl+PDT—Photodynamic therapy following syringe irrigation with NaOCl, (4) PUI+PDT, (5) Control—Syringe irrigation with saline. Colony-forming units were counted and bacterial reduction was calculated for each treatment group. Results: All treatments led to significant reductions in the bacterial load compared to the control group. PUI and PUI+PDT led to the complete elimination of the bacteria from the root canals. NaOCl and NaOCl+PDT treatments reduced the bacteria by 99.9% and 99.5% respectively. NaOCl+PDT was significantly less effective in reducing the bacteria compared to other treatment groups. There were no significant differences between the NaOCl, PUI, and PUI+PDT groups. Conclusion: Passive ultrasonic irrigation with or without the combination of Photodynamic therapy completely eradicated the bacteria. The use of PDT as an adjunction to NaOCl syringe irrigation and PUI did not enhance their antibacterial effect. DOI: 10.34172/jlms.2021.81